Synthesis, characterization and in vitro biological studies of novel Nitrilo derivatives of N-substituted phenyl piperazine - Idries AL-Mashkor (مجلة علوم ذي قار, 2019)
Nitrilo derivatives of N-alkyl and N-aryl phenyl piperazine have been synthesized and screened for antibacterial and antifungal activities. All the synthesized compounds showed the antibacterial activity against pathogenic strains of Staphylococcus aureus (MTCCB 737), Pseudomonas aeruginosa (MTCCB 741),Streptomyces epidermidis (MTCCB 1824) and Escherichia coli(MTCCB 1652) and antifungal activity against pathogenic strains of Aspergillus fumigatus (ITCC 4517), Aspergillus flavus (ITCC 5192) and Aspergillus niger (ITCC 5405). All compounds showed mild to moderate antimicrobial activity. However, compounds 3c, 4a and 6 showed potent antibacterial activity against pathogenic strains used in the study. Compounds 3a, 3b, 4b, and 4d showed mild to moderate antifungal activity against Aspergillus pathogenic strains.